Perioperative and long-term survival outcomes of laparoscopic versus open hepatectomy for BCLC stage A large hepatocellular carcinoma patients in difficult segments: A two-centre, propensity score matching analysis - Ding, Dong-yang; Liu, Lei; Lin, Kong-ying; Gan, Xiao-jie; Guo, Xing-gang; Ding, Wen-bin; Sun, Da-peng; Li, Wen; Tao, Qi-fei; Gu, Fang-ming; Guo, Wei-xing; Zeng, Yong-yi; et al. (Frontiers in Oncology, 2023)
Background The differences in short- and long-term outcome between laparoscopic liver resection (LLR) and open liver resection (OLR) for BCLC stage A large hepatocellular carcinoma (HCC) in difficult segments (I, IVa, VII, VIII) remain unclear. This PSM two-centre study aimed to compare perioperative and long-term survival outcomes of LLR with OLR for this HCC. Methods HCC patients with BCLC stage A who underwent OLR or LLR in two medical centres were enrolled in the study. PSM analysis was performed to match patients between the LLR cohort and OLR cohort. Survival was analysed based on the Kaplan–Meier method. Independent risk factors were identified by Cox regression. Results After PSM, 35 patients remained in the LLR cohort, and 84 remained in the OLR cohort. Patients in the LLR cohort had more intraoperative blood loss (p=0.036) and shorter hospital stays after surgery (p<0.001). The LLR cohort and OLR cohort had no difference in intraoperative blood transfusion, surgical margin or postoperative short-term outcomes. The OS and RFS were not significantly different between the two cohorts. The OS and RFS of these two cohorts were not different in the subgroup analysis. Surgical margin was identified as an independent risk factor for tumour recurrence. Conclusion For BCLC stage A large HCC patients with lesions in difficult segments, LLR was feasible and had shorter hospital stay than OLR. In addition, a surgical margin ≥1 cm could significantly decrease the recurrence probability for large HCC located in different segments without compromising short-term outcomes.